Impact of Humidity on In Vitro Human Skin Permeation Experiments for Predicting In Vivo Permeability. Issue 12 (13th October 2015) - Ishida, Masahiro; Takeuchi, Hiroyuki; Endo, Hiromi; Yamaguchi, Jun‐Ichi
Abstract : In vitro skin permeation studies have been commonly conducted to predict in vivo permeability for the development of transdermal therapeutic systems (TTSs). We clarified the impact of humidity on in vitro human skin permeation of two TTSs having different breathability and then elucidated the predictability of in vivo permeability based on in vitro experimental data. Nicotinell ® TTS ® 20 and Frandol ® tape 40mg were used as model TTSs in this study. The in vitro human skin permeation experiments were conducted under humidity levels similar to those used in clinical trials (approximately 50%) as well as under higher humidity levels (approximately 95%). The skin permeability values of drugs at 95% humidity were higher than those at 50% humidity. The time profiles of the human plasma concentrations after TTS application fitted well with the clinical data when predicted based on the in vitro permeation parameters at 50% humidity. On the other hand, those profiles predicted based on the parameters at 95% humidity were overestimated. The impact of humidity was higher for the more breathable TTS; Frandol ® tape 40mg. These results show that in vitro human skin permeation experiments should be investigated under realistic clinical humidity levels especially for breathable TTSs. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4223–4231, 2015